ORGANIZATION OF NOTARY BUSINESS IN SIBERIA BEFORE 1896: THE YENISEI PROVINCE - T. G. Karchaeva (Вестник Кемеровского государственного университета, 2018)
The current paper features organization and operation of notaries in Siberia before 1896. The data obtained have revealed that the Statute of Notaries reached Siberia some thirty years after it had been issued in Central Russia in 1866. The article contains information about the development of the history of Notarial Institute in the Yenisei province before and after the Siberian Notary Reform of 1896. It has been concluded that Siberia had regional peculiarities in its management in the pre-revolutionary period of Russian history. In the XVIII century notary functions were performed by clerks, bailiffs and "weeklings", after 1822 – by officials of city councils and police employees (e.g. the city of Turukhansk). The author notes that the rapid social and economic changes in Siberia predetermined the need for the development of the pre-reform notary as an independent legal institution. Archival materials reveal that the first notary began his work in Krasnoyarsk as late as in 1883, and he was not a state servant, the way it was in Central Russia, but was elected by the local municipal authorities; what is more, neither authorities nor society had any influence on his activities. It was concluded that the pre-1896 Siberian notaries had a number of regional features that played their role in the pre-revolutionary period of Russian history.